A survey of pet feeding practices of dog owners visiting a veterinary practice in Colombo, Sri Lanka. Issue 2 (10th February 2016) - Seneviratne, Maheeka; Subasinghe, Dynatra W.D.; Watson, Penny J.
Abstract: In Sri Lanka, home‐cooked diets are often fed due to the cost and poor availability of commercial diets. Milk has traditionally been a popular food to give to dogs in this country. There is a recent perceived increase in the number of owners choosing commercial diets for their pets. This study aimed to determine how dog owners visiting a single veterinary practice in Colombo fed their pets. We hoped that this would help achieve a general understanding of pet feeding practices in Sri Lanka and gain some basic demographic information on the owned dog population. The study was conducted via questionnaires distributed to pet owners visiting a first opinion and referral practice in Colombo. Hundred questionnaires were collected and analysed, 69% of study dogs were neutered, 42% of dogs were fed only home‐cooked food, while 18% were fed only commercial food. About 40% of dogs were fed a mixture of commercial and home‐cooked food, 49% of dogs were fed milk as a separate meal in addition to their normal diet and 57% of dogs received dietary supplements. Dogs consuming commercial food for more than half their intake were no less likely ( P = 0.75) to receive dietary supplements than dogs fed homemade food for more than half their diet. This study provides some basic information regarding the feeding practices and demographics of the owned dog population in one Sri Lankan city, Colombo, highlighting some areas of concern. Abstract : This article describes how and what pet dogs are fed in Sri Lanka and attempts to gain an understanding of the use of commercial diets vs. homemade diets for dogs. It also provides some basic demographic information on the pet dog population in Colombo, Sri Lanka.